Rice pathogens intercepted on seeds originating from 11 African countries and from the USA - Dossou, B.; Silué, D. (International Seed Testing Association, 2018)
1,916 rice seed samples from 11 African countries and the USA were tested for the presence of pathogenic microorganisms or those affecting seed quality. Bacillus spp., Pantoea spp., Sphingomonas sp. and the fungi Acremoniella sp., Alternaria sp., Aspergillus flavus, A. fumigatus, A. niger, Chaetomium sp., Curvularia sp., Fusarium oxysporum, F. solani, Fusarium sp., Helminthosporium sp., Microdochium oryzae, Nigrospora oryzae, Penicillium sp., Pestalotia sp., Phoma sp., Magnaporthe oryzae, Rhizopus sp., Sarocladium sp. and Tilletia barclayana were isolated. The highest incidence values were obtained with Curvularia sp., Microdochium oryzae, A. flavus, F. solani and Nigropora sp. In contrast, these fungi were not isolated from seeds of many countries with Togo having the least affected seeds (nine out of the 24 potential organisms diagnosed). The highest frequencies of these organisms were found on seed samples from Benin (20/22), Burundi and Tanzania (19/24), and Senegal (18/24). Across countries, A. flavus, A. fumigatus, Curvularia sp., F. solani, Nigropora sp., Rhizopus sp. and Microdochium oryzae were the most frequently isolated organisms. Concerning the major diseases, blast was diagnosed only once despite the high number of samples tested.